Effects of combined cortical and acoustic stimuli on muscle activity. - Fisher, R; Sharott, A; Kühn, A; Brown, P (2004)
Hitherto, it has proven difficult to investigate interactions between cerebral and brainstem motor systems in the human. We hypothesised that transcranial magnetic stimulation (TMS) centred over the dorsal premotor and primary motor cortices might elicit net facilitatory cortico-reticular effects that could interact at the level of the brainstem with a habituated startle to give a reticulospinal discharge and electromyographic (EMG) response with a longer latency than the direct corticospinal response. Conversely, any reticulo-cortical activity evoked by a habituated startle should influence the size of the direct response to cortical TMS. EMG was recorded from active left deltoid muscle in nine healthy volunteers. Acoustic stimulation was delivered binaurally through headphones and repeated until the startle response was habituated. When TMS was centred over the right dorsal premotor or primary motor cortices and delivered 50 ms after the habituated acoustic stimulus, the contralateral direct motor evoked potential was inhibited, compared with the response elicited by TMS alone. The contralateral silent period was shortened and associated with less of a decrease in EMG levels relative to TMS alone. Indeed, an actual increase in EMG over baseline levels occurred in the later half of the silent period in all subjects. We conclude that both cortico-reticular and reticular-cortical effects could be elicited in deltoid through the combination of acoustic stimulation and TMS at short interstimulus intervals. Effects were similar with TMS over premotor and primary motor cortex.